Tasa de interés de créditos otorgados por la banca múltiple en el Perú - Cortez Cortez, Gaby (2012)
The structure of lending rates charged in Peru’s banking system shows an inverse relation to the economic scale of the companies that receive the loans from banks, ie establishing preferential lending rates to customers under more economic scale in the market for goods and services, and lending rates higher for customers with smaller scale of business.